Metallogels Self‐Assembled from Linear Rod‐Like Platinum Complexes: Influence of the Linkage. Issue 11 (2nd February 2015) - Chen, Mingming; Wei, Chengsha; Wu, Xibo; Khan, Majid; Huang, Ningdong; Zhang, Guobin; Li, Liangbin
Abstract Two linear rod‐like platinum complexes, which only differed in the linkage, were prepared. They both self‐assemble into metallogels in nonpolar solvents; however, a very big contrast was observed. Unexpectedly, a much weaker gel was acquired upon replacing the ester linkage by an amide group. The intermolecular hydrogen bonding offered by the amide motif leads to a different stacking fashion and mechanism. The results demonstrated herein contribute to the rational design of metallogels as well as other functional supramolecular materials.